How valuable is MFN treatment to the Philippines? - Clarete, Ramon L. (1995)
This paper attempts to measure the benefit to the Philippines of its availment of theWTO-MFN treatment. The methodology involves computing the reduction in the country's merchandise exports if the country loses MFN treatment, depicted in this paper as an increase by five percentage points of the tariff rates in the importing countries on such exports.The World Bank-UNCTAD's SMART computer program is used for this purpose. The foregone exports are then introduced as a shock to an applied general equilibrium model of the Philippines to calculate the income lost due to reduced exports. The result of this exercise does confirm that the country may stand to lose up to eighty percent of its export earnings. Even at a conservative loss of only twenty percent of its exports, in consideration of the possible bilateral deals that may continue MFN treatment on selected merchandise exports, the Philippines may forgo an income of nearly eight percent.
Keywords: World Trade Organization; Favored nation clause